Cloaca-Like Anomalies in the Male: A Report on Two Cases - Amr AbdelHamid AbouZeid; Shaimaa Abdelsattar Mohammad; Marco Rady Sos; Nader Nassef Guirguis; Heba A. Mahmoud; Manal El-Mahdy (Georg Thieme Verlag KG, 2022)
"Cloaca" is a term used to describe an anomaly in the female where a single orifice is located in the perineum draining both urogenital and gastrointestinal tracts. Few reports used the same term "cloaca" to describe the counterpart anomaly in the male. We present two "male" cases of anorectal anomalies associated with significant penile deformity (caudally displaced penis) that were managed during the period between January 2010 and September 2021. Characteristically, both cases had a single "central" perineal orifice. The latter was located anterior to the predestined site of the normal anus and just beneath a caudally positioned hypospadiac phallus. The caudal displacement of the penis was strikingly obvious by the presence of severe form of penoscrotal transposition. Both cases were associated with a perineal swelling (hamartoma) just beside the central perineal orifice. The urethra was very short (like that in the female), besides the single perineal orifice, which makes the presentation very similar to cloacal anomalies.